The Effect Of The Adapted Physical Activity Program On Some Health-related Components Of Physical Fitness For Patients With Hemiplegic Paralysis Resulted From Stroke - Chaalal , ismail Mustapha (Journal of Sport Science Technology and Physical Activities, 2021)
The study aims to identify the effect of a program of adapted sports activities on some health-related physical fitness elements for patients with hemiplegic paralysis as a resulted of the blood stroke. For this purpose, we used the experimental method to design this research in two groups; one experimental and the other a control group with pre- and post-treatment on a sample of 10 patients with stroke paraplegia. Their age ranges between (45 years - 60 years), the duration of the program was (24) weeks.After collecting the results and treating them statistically, it was concluded that the modified sports activities program has a positive effect on restoring the movement competence of patients with paraplegia and shortening the period of time for recovery. The researcher recommended the use of specialists in the field of adapted physical activity to participate in the design of rehabilitation programs.